ANALISIS SEBARAN RADIASI HAMBUR CT SCAN 128 SLICE TERHADAP PEMERIKSAAN CT BRAIN - Purwatiningsi, Purwatiningsi; Prasetio, Hari Eko (Sainstek : Jurnal Sains dan Teknologi, 2016)
The use of high dose levels in CT Scan Brain produce distribution scattered radiation originating from the patient. This study was conducted to determine the distribution of scattered radiation at a particular point on the CT scan to obtain the curve isodose. Using Experimental Methods researchers conducted measurements of the distribution of the scattering radiation at 128 Slice CT Scan of the Brain CT examination. Thermoluminescent dosimeter (TLD) is used to measure the distribution of scattered radiation and use as a phantom object head. Eksposi parameters used are Brain CT program. Take 19 points to be measured. Using a point distance of 1, 2 meters, 3 meters from the gantry CT Scan. The results showed a minimum value of the distribution of the scattering radiation at the measurement point at a distance of 1 meter, 2 meters. 3 meters is at point A is the right side of the gantry and a maximum distribution at point C which is the examination table.Key words: CT Scan, distribution of scattered radiation, isodose curves